Strategic Factors Influencing the Sustainability of Indonesia’s Food Estate Program in Central Kalimantan: A MICMAC Approach - Ompusunggu, Dicky Perwira; Rakhmawati, Dewi; Husnatarina, Fitria; Suherman; Simbolon, Tiur Roida; Nasrida, Muhammad Farras; Neneng, Sunaryo; Sri Desmita Sihombing, Putri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
The Food Estate program, a national initiative to strengthen food security through increased food production on peatlands, faces substantial challenges, including difficult land conditions, inadequate infrastructure, and potential social and environmental impacts such as land degradation and community displacement. This study aims to identify key factors influencing the sustainability of the Food Estate program in the Kapuas and Pulang Pisau districts, Central Kalimantan, by employing the MICMAC method (Matrix of Crossed Impact Multiplications Applied to a Classification). Primary data were collected through interviews with 50 respondents, consisting of 20 farmer group members and 30 individuals from relevant institutions and stakeholders. The findings reveal that government policies and infrastructure are the dominant factors directly and indirectly influencing the program's success. Both the Matrix of Direct Influences (MDI) and the Matrix of Indirect Influences (MII) consistently identify government policies and infrastructure as key driving variables. Conversely, variables such as local economy and agricultural technology demonstrate a high level of dependence on other factors, particularly government policies and infrastructure. These results underscore the importance of strong policy frameworks and robust infrastructural support for program viability. Recommendations include the need for sustainable policy enhancement, accelerated development of supporting infrastructure, improved market access, and adaptive technology training for farmers. Addressing social and environmental considerations alongside economic factors will be crucial for the long-term success and sustainability of the Food Estate program in Central Kalimantan.